Drug survival of biologic therapy in a large, disease‐based registry of patients with psoriasis: results from the Psoriasis Longitudinal Assessment and Registry (PSOLAR). (30th March 2016) - Menter, A.; Papp, K.A.; Gooderham, M.; Pariser, D.M.; Augustin, M.; Kerdel, F.A.; Fakharzadeh, S.; Goyal, K.; Calabro, S.; Langholff, W.; Chavers, S.; Naessens, D.; et al.
Abstract: Background : Drug survival is a marker for treatment sustainability in chronic diseases such as psoriasis. Objective: The aim of these analyses was to assess survival of biologic treatments in the PSOriasis Longitudinal Assessment and Registry (PSOLAR). Methods: PSOLAR is a large, prospective, international, disease‐based registry of patients with psoriasis receiving (or eligible for) systemic therapy in a real‐world setting. Drug survival is defined as the time from initiation to discontinuation (stop/switch) of biologic therapy on registry. The number of patients who discontinued each treatment and the duration of therapy were recorded. Using Kaplan–Meier survival curves and Cox‐regression analyses [hazard ratios (HR) and 95% confidence intervals (CIs)], time to discontinuation was compared across cohorts undergoing first‐, second‐ or third‐line treatment with ustekinumab, infliximab, adalimumab or etanercept. Results: As of the 2013 data cut, 12 095 patients with psoriasis were enrolled in PSOLAR. Of the 4000 patients initiating any new biologic therapy, approximately 3500 started a first‐line, second‐line or third‐line biologic therapy during the registry. Lack of effectiveness was the most common reason for discontinuation across biologic therapies. Based on the multivariate analysis, significantly shorter times to discontinuation were observed for infliximab [HR (95%CI) = 2.73 (1.48 – 5.04), P = 0.0014]; adalimumab [4.16 (2.80 – 6.20), P < 0.0001]; and etanercept [4.91 (3.28 – 7.35) P < 0.0001] compared with ustekinumab [reference treatment]) for first‐line biologic use; results were similar for treatment effects for second/third‐line therapies. Although limited in power, analyses in patients with concurrent psoriatic arthritis confirmed by a rheumatologist reflect observations in the overall psoriasis population. Conclusion: Drug survival was superior for ustekinumab compared with infliximab, adalimumab and etanercept in patients with psoriasis.